„Ja” na pięć głosów rozpisane? Wielogłosowość madrygału od 1950 roku - Micał, Dominika (Res Facta Nova, 2021)
Surprisingly, since 1950, at least 500 works connected to the madrigal, and among them at least 454 madrigals, have been written. Unfortunately, a comprehensive musicological or theoretical-musical approach to that issue has been lacking so far. Using the genre studies perspective, the article aims to show how some composers working in the second half of the 20th–century and in the 21st–century respond to the early madrigal in terms of one of the most important madrigal characteristics – its polyphonic scoring and texture. That aspect, criticised by theorists at the end of the 17 th century, became the source of diverse musical reinterpretation in contemporary pieces by, among others: Luciano Berio, Christophe Bertrand, Harrison Birtwistle, George Crumb, Beat Furrer, Roman Haubenstock-Ramati, Paul Hindemith, Mauricio Kagel, György Ligeti, Luigi Nono, Henri Pousseur, Grażyna Pstrokońska-Nawratil, John Rutter, Johannes Schöllhorn, Salvatore Sciarrino, Marek Stachowski, Alfred Schnittke, Pēteris Vasks, Agata Zubel. A number of aspects of polyphony are taken into consideration: type of polyphonic means (canons, fugue, passacaglia, etc.), their function (structural, semantic, emotional, etc.), and their meaning (c.f. their role in the process of constructing the subject of given works).